E-LAS (Letter of Active Status) Pada Biro Administrasi Akademik - Sumarhadi Sumarhadi; Iskandar Fitri; Nurhayati Nurhayati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The Academic Administration division (BAA) plays a role in the process of issuing student certificates at the National University. Although the data has been computerized, the process of issuing the letter is still manual so it is less effective and efficient. Students must come to the BAA unit to apply for the issuance of a student certificate, including for data correction purposes if needed. This will require more effort for students in terms of time, energy and material. This research is to design a Web-Based Student Certificate Making System that can simplify the service process and submission of a certificate for students at the National University. This system is integrated and responsive and is accessed online. The application was developed with the waterfall model and utilizes the Unified Modeling Language (UML) tool and uses the PHP programming language. The result of this study is the existence of a web-based certificate application design that can facilitate students in obtaining student certificates at the National University. The results of testing the application using the white-box and black-box methods, indicate that the logic and functionality of the application is running well and can be used by the BAA unit of the National University.